The effects of climate change on agriculture and food security in Africa - Wiebe, Keith D.; Sulser, Timothy B.; Mason-D'Croz, Daniel; Rosegrant, Mark W. (International Food Policy Research Institute, 2017)
Chapter 2 describes the context in which policy and investment decisions will have to take place, finding that in the years leading up to 2050, African countries will continue to grow, and many will reach middle-income status. As the agricultural sector grows, it will need to become technologically more sophisticated to withstand the vagaries of climate and market conditions. Key to future growth will be regionally tailored, evidence-based efforts to address increased regional market integration and the regional shifts in agroecological conditions.